THE IMPACT OF STRENGTH TRAINING WITH A SLOW ECCENTRIC PHASE OF MOVEMENT ON LOWER LIMB MOBILITY, SPRINT AND JUMP FOR DISTANCE PERFORMANCE - Dariusz Mikolajczyk; Patryk Szary; Sebastian Rutkowski (Slovak Journal of Sport Science, 2021)
The aim of the study was to assess the impact of strength training with a slow eccentric phase of movement on the range of mobility of the lower limb joints, sprint performance and power of football players. The study included 15 men aged: 21 years ± 5, height: 175 cm ± 10, body weight: 70 kg ± 18, BMI: 22.9 ± 6.6 who train football in the senior team of the LZS Victoria Żyrowa club. The mobility of the lower limb in the sagittal plane was examined. A sprint performance test was carried out over a distance of ten and thirty meters. In order to test the competitors' power, a jump for distance test was performed. Circuit training consisting of 9 strength exercises was held once a week for a period of six weeks. The competitors' task was to perform 4 full circuits. The training program included a command to perform the concentric phase of movement at a rapid pace. In the eccentric phase, movement was to be controlled and extended. The training used showed a significant impact on increasing the range of joint mobility for football players. Muscle groups most at risk of injury like hamstrings, hip flexors, plantar flexors of the foot have been functionally stretched. The training had also a positive effect on sprint performance and increasing the player's power, tested by jump for distance.